Piperine Attenuates Lithocholic Acid-Stimulated Interleukin-8 by Suppressing Src/EGFR and Reactive Oxygen Species in Human Colorectal Cancer Cells - Shinan Li; Thi Thinh Nguyen; Trong Thuan Ung; Dhiraj Kumar Sah; Seon Young Park; Vinoth-Kumar Lakshmanan; Young Do Jung (MDPI AG, 2022)
Piperine, a natural alkaloidal pungent product present in pepper plants, possesses the properties of anti-inflammatory and anti-metastasis. Lithocholic acid is a monohydroxy-5beta-cholanic acid with an alpha-hydroxy substituent at position 3; it is a secondary bile acid that plays a pivotal role in fat absorption, and has been discovered to mediate colorectal cancer (CRC) cell invasion and migration. However, the effect of piperine on angiogenesis has been poorly investigated. In the current study, we examined the role of piperine on LCA-stimulated angiogenesis by measuring interleukin-8 (IL-8) expression; moreover, we revealed the potential molecular mechanisms in CRC cells. Here, we showed that piperine inhibited LCA-stimulated endothelial EA.hy926 cell angiogenesis in a conditioned medium obtained from colorectal HCT-116 cells. Experiments with an IL-8 neutralizer showed that IL-8 present in the conditioned medium was the major angiogenic factor. Piperine inhibited LCA-stimulated ERK1/2 and AKT via the Src/EGFR-driven ROS signaling pathway in the colorectal cell line (HCT-116). Through mutagenesis and inhibitory studies, we revealed that ERK1/2 acted as an upstream signaling molecule in AP-1 activation, and AKT acted as an upstream signaling molecule in NF-κB activation, which in turn attenuated IL-8 expression. Taken together, we demonstrated that piperine blocked LCA-stimulated IL-8 expression by suppressing Src and EGFR in human CRC HCT-116 cells, thus remarkably attenuating endothelial EA.hy926 cell tube formation.